Blow-up phenomena arising in a reaction-absorption-diffusion equation with gradient diffusivity - Chaves, M. (Український математичний вісник, 2004)
We study the blow-up phenomena arising in a p-laplacian equation with reaction and absorption terms. We show that there exists a unique blowing-up approximate self-similar solution which describe the asymptotic singular behaviour of a wide class of solutions. As a consequence, we conclude that in this class, the absorption became negligible in finite time in the competition between the reaction and the absorption terms.